2017
DOI: 10.1039/c6ra28237g
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of rosmarinic acid in rats by LC-MS/MS: absolute bioavailability and dose proportionality

Abstract: a Rosmarinic acid (RA), one of the main bioactive compounds of Rosmarinus officinalis L., exhibits diverse pharmacological effects. However, its oral absolute bioavailability and dose proportionality in vivo have not been comprehensively studied. In the present study, a validated LC-MS/MS method was developed for the determination of RA in rat plasma. Pharmacokinetic parameters were obtained following oral and intravenous dosing using DAS 3.0 software. Absolute bioavailability in rats was determined by compari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
22
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 32 publications
4
22
1
Order By: Relevance
“…Important aspect to consider is that the current work was performed with rat aortic VSMC, and to exclude species differences the effects of RAME need to be also validated with human VSMC in future experiments. On a systemic level, RA was reported to have poor oral bioavailability (0.91–1.69% in rats), and there is no report about the metabolism and pharmacokinetics of RAME. While these data on bioavailability currently shadow the potential physiological nutritional relevance of the reported findings, RAME, when applied locally, did show in vivo efficacy in a mouse femoral cuff model and significantly inhibited neointima formation.…”
Section: Discussionmentioning
confidence: 99%
“…Important aspect to consider is that the current work was performed with rat aortic VSMC, and to exclude species differences the effects of RAME need to be also validated with human VSMC in future experiments. On a systemic level, RA was reported to have poor oral bioavailability (0.91–1.69% in rats), and there is no report about the metabolism and pharmacokinetics of RAME. While these data on bioavailability currently shadow the potential physiological nutritional relevance of the reported findings, RAME, when applied locally, did show in vivo efficacy in a mouse femoral cuff model and significantly inhibited neointima formation.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several pharmacokinetic studies concerning RA, CA and FA have been reported, including single‐compound, herbal extract and compound prescription of TCM. Some studies have been performed on the quantitative determination of one or more of these three components (Guo et al, 2019; Konishi, Hitomi, Yoshida, & Yoshioka, 2005; Min et al, 2018; Qu et al, 2020; Shi et al, 2020; Wang et al, 2017; Zhang, Xu, & Zhan, 2018). However, the simultaneous determination of pharmacokinetic profiles for RA and its two bioactive metabolites CA and FA after oral administration of RA has rarely been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated high doses of Melissa officinalis extract (containing 120 mg of rosmarinic acid for 16 weeks) have been reported to improve cognitive function in patients with mild-to-moderate Alzheimer’s disease [ 35 ]. To determine the acceptable daily intake dose of rosmarinic acid, the pharmacokinetics and tolerability of high dose intake of rosmarinic acid (50 mg/kg in rats and 500 mg in humans) have been investigated [ 9 , 13 ]. Rosmarinic acid showed low oral bioavailability (0.9–1.7% in the oral dose range from 12.5 mg/kg to 50 mg/kg in rats) [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rosmarinic acid showed low permeability, and 0.03–0.06% of rosmarinic acid was absorbed in Caco-2 cells via paracellular pathway [ 12 ] and it underwent glucuronide metabolism during the absorption phase [ 2 ]. In the dose range of 12.5–50 mg/kg, the absolute bioavailability of rosmarinic acid was 0.9–1.7% in rats, and their AUC did not show dose proportionality [ 13 ]. Oral administration of rosmarinic acid (50 mg/kg) in combination with piperine (20, 40, 60, and 80 mg/kg) significantly increased the AUC of rosmarinic acid together with a significant decrease of rosmarinic acid glucuronide [ 14 ].…”
Section: Introductionmentioning
confidence: 99%